Deficient and multiple points of maps into a manifold - Goncalves, Daciberg L.; Monis, Thais F.M. [UNESP]; Spiez, Stanis Law (My University, 2020)
The notion of Hopf's absolute degree is classically defined for mappings between manifolds of the same dimension, even when they are not necessarily orientable. In this paper, we extend such notion for mappings from more general spaces into manifolds. Once we have stablished a version of Hopf's absolute degree for certain maps f: X → M, where M is a manifold but X need not be, we study the sets of deficient and multiple points of f. In case of the set of deficient points, we estimate its dimension. For multiple points, we study its density in X, and we also provide examples where its complement is dense.